Changes in Landscape Pattern and an Ecological Risk Assessment of the Changshagongma Wetland Nature Reserve - Yang, Cai; Deng, Wei; Yuan, Quanzhi; Zhang, Shaoyao (Frontiers in Ecology and Evolution, 2022)
Changshagongma Wetlands is a Chinese National Nature Reserve. It was designated as a Ramsar Wetland of International Importance in 2018. Here we examined four periods (1992, 2002, 2013, and 2020) of remote sensing image data to analyze the changes in wetland landscape patterns and the ecological risk in Changshagongma National Nature Reserve over the past 30 years. Results shows that wetlands account for approximately 30% of the study area, and swamp meadow is the main type of wetland, accounting for approximately 95% of total wetland area. In terms of landscape patterns, wetland fragmentation declined, wetland patch shapes became less complicated, and spatial connectivity increased. The landscape fragmentation of non-wetland alpine meadows was reduced. The patches of sandy grasslands tended to be regular, and their spatial connectivity was reduced. The wetland areas of high ecological risk are concentrated in the central and southern parts of Changshagongma Nature Reserve. Low-risk areas are mainly concentrated in the contiguous swamp meadows in the northwest and wetlands in the southwest. From 1992 to 2020, the level of ecological risk of Changshagongma Nature Reserve showed a “∧”-shaped trend, with the highest risk in 2002 and the lowest risk in 2020. Among the selected indicators, climate conditions constituted the main factor affecting the ecological risk of Changshagongma Nature Reserve, followed by topographical conditions, and human activities were the least influential. Over the past 30 years, the temperature and precipitation in the study area both increased significantly. The climate in the study area can be roughly divided into two different periods by the year 2002, and the climate has been changing from cold and dry to warm and wet. The ecological environment of the study area is affected by both natural and human activities. Cold and dry climatic conditions and uncontrolled grazing accelerate the destruction of the wetland ecological environment, and warm and wet climatic conditions and ecological conservation policies are conducive to the ecological restoration of the wetlands. In general, the wetland landscape structure in the study area has become less complex, landscape heterogeneity has decreased, and the ecological quality has improved.